Controlling correlations in the Rydberg-dressing six-wave mixing process. (1st December 2016) - Zhang, Zhaoyang; Ma, Danmeng; Liu, Junfeng; Ahmed, Irfan; Tian, Hao; Che, Junling; Tang, Haijun; Raza, Faizan; Zhang, Yanpeng
Abstract: We report the experimental observation of intensity noise correlation between six-wave mixing (SWM), fluorescence and probe transmission signal in a coherently prepared Rydberg atomic ensemble. With the assistance of the electromagnetically induced transparency (EIT) technique, the Rydberg SWM is generated with high efficiency. Then the correlation between the probe transmission and SWM, the anti-correlation between the probe and fluorescence, and the anti-correlation between SWM and fluorescence occur, with these being caused by the enhanced dispersion and nonlinearity in the Rydberg-EIT medium. Such intensity correlation can be effectively controlled by the strong Rydberg-dressing effect. This investigation can potentially contribute to the further study of multi-field quantum correlations and anti-correlations via atomic spin coherence.